Laboratory Evaluation of Partial Depth Patching Materials for Use in Winter Climates. Issue 1 (January 2015) - Dailey, Jay; Dave, Eshan V.; Musselman, Eric; Kostick, Robert
Over the course of their service life, concrete pavements undergo significant traffic and climatic loads, which lead to a gradual accumulation of damage. This accumulation of damage and distress comes from the effects of changing weather conditions (e.g., temperature, moisture) and continuous vehicular traffic. Repeated environmental and traffic loading leads to cracking and spalling of the concrete at the joint edges. States in the northern portion of the United States and the provinces of Canada have climates that fluctuate greatly in temperature throughout the seasons. Greater temperature differentials cause greater deflections in rigid pavements; these deflections lead to more prevalent spalling and a greater need for partial depth repair. Many U.S. state departments of transportation (DOTs) use partial depth repair as routine practice to maintain concrete pavements (e.g., the DOTs of Minnesota, North Dakota, South Dakota, Idaho, Montana, Washington, and Wisconsin). Enhanced acceptance criteria of rapid set cementitious materials for use in partial depth repair are needed. The purpose of this study was to investigate laboratory tests, recommended by ASTM C928 and others, for inclusion in the acceptance specifications for patching materials.